The use of e-learning resources in the process of teaching biology - Sardor Soyibjonov Soyibjon oʻgʻli (Euro Asian Journal Publishing, 2023)
This article explores the integration of e-learning resources in the teaching of biology. It investigates the methods, results, and implications of incorporating online tools and materials into biology education, emphasizing the benefits for both educators and students.
Keywords: E-Learning; biology education; online resources